Automatic Plant Watering System - Shahidan, Muhammad Izzan; Jamsari, Muhammad Harith Isma; Mohd Aminnudin, Muhamad Amirul Amin; Kassim, Noraniah (Multidisciplinary Applied Research and Innovation, 2022)
This paper presents an automatic plant watering device based on ESP-WROOM-32 module with ESP32‑D0WDQ6 chip or in short form, it is called ESP32 for home, office and small uses, establish a prototype of automatic plant watering system and make the process of watering easier for the owner of the plants. In daily operations related to farming or gardening watering is the most important cultural practice and the most labour-intensive task. Growing a plant has always been a favourite activity for people around the globe but taking care of it is a different story to be unfold. The lack of essential things for plants such as water, fertilizer and sunlight can fail the process of growth of a plant. Most of people really forget about this when they have busy schedule for the entire week or they are not home. This device should be capable to water the plant automatically at a specified time. This system is targeted for working people and have a tight daily schedule. It is completely practical for home usage. In order to replace manual activities in watering plant and also making the owner’s work easier, -Ari, an automatic plant watering system are the solution for the problem above. For application of automatic plant watering system, it used combinations of water pumps, filters, nozzles and pipes. ESP32 microcontroller which it is programmed to sense the moisture content of the soil over a period of time. When the moisture content is less than the limit predefined, it will start supplying the desired amount of water until it reaches the limit. Thus, when the soil is dry the pump will automatically water the fields and when the soil is wet the pump will automatically switch off, thereby eradicate the need for manpower and conserve time.